2017
DOI: 10.3390/s17040857
|View full text |Cite
|
Sign up to set email alerts
|

Range Analysis of Thermal Stress and Optimal Design for Tungsten-Rhenium Thin Film Thermocouples Based on Ceramic Substrates

Abstract: A thermal stress range analysis of tungsten-rhenium thin film thermocouples based on ceramic substrates is presented to analyze the falling off and breakage problems caused by the mismatch of the thermal stresses in thin film thermocouples (TFTCs) and substrate, and nano-indentation experiments are done to measure and calculate the film stress to compare with the simulation results. Optimal design and fabrication of tungsten-rhenium TFTCs based on ceramic substrates is reported. Static high temperature tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The stress finite element model was set to design the size parameters of the TFTCs [21]. In the thermal stress finite element analysis (FEA) by ANSYS (ANSYS Inc., Berkeley, CA, US), the isotropic, thermoplastic and orthotropic behavior of the material was considered.…”
Section: Resultsmentioning
confidence: 99%
“…The stress finite element model was set to design the size parameters of the TFTCs [21]. In the thermal stress finite element analysis (FEA) by ANSYS (ANSYS Inc., Berkeley, CA, US), the isotropic, thermoplastic and orthotropic behavior of the material was considered.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, temperature sensors are indispensable for obtaining accurate operational temperatures. Not only do these sensors serve as a basis for enhancing engine efficiency, but they also facilitate the real-time monitoring of engine operational status [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten-rhenium TFTCs exhibit superior performance due to their high melting point of approximately 2800 °C and ease of oxidation [ 17 ]. Although we previously demonstrated that high temperature failure can be avoided using an alumina protective layer on tungsten-rhenium TFTCs, the drift rate (DT) is high (9.6 °C/h), resulting in low thermoelectric stability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%